Association between intra-operative cardiac arrest and country Human Development Index status: a systematic review with meta-regression analysis and meta-analysis of observational studies* - Braz, L. G. [UNESP]; Einav, S.; Heesen, M. A.; Betini, M. [UNESP]; Corrente, J. E. [UNESP]; Pacchioni, M. [UNESP]; Cury, J. B. [UNESP]; Braz, M. G. [UNESP]; Braz, J. R.C. [UNESP] (Wiley, 2021)
Intra-operative cardiac arrests differ from most in-hospital cardiac arrests because they reflect not only the patient's condition but also the quality of surgery and anaesthesia care provided. We assessed the relationship between intra-operative cardiac arrest rates and country Human Development Index (HDI), and the changes occurring in these rates over time. We searched PubMed, EMBASE, Scopus, LILACS, Web of Science, CINAHL and SciELO from inception to 29 January 2020. For the global population, rates of intra-operative cardiac arrest and baseline ASA physical status were extracted. Intra-operative cardiac arrest rates were analysed by time, country HDI status and ASA physical status using meta-regression analysis. Proportional meta-analysis was performed to compare intra-operative cardiac arrest rates and ASA physical status in low- vs. high-HDI countries and in two time periods. Eighty-two studies from 25 countries with more than 29 million anaesthetic procedures were included. Intra-operative cardiac arrest rates were inversely correlated with country HDI (p = 0.0001); they decreased over time only in high-HDI countries (p = 0.040) and increased with increasing ASA physical status (p < 0.0001). Baseline ASA physical status did not change in high-HDI countries (p = 0.106), while it decreased over time in low-HDI countries (p = 0.040). In high-HDI countries, intra-operative cardiac arrest rates (per 10,000 anaesthetic procedures) decreased from 9.59 (95%CI 6.59–13.16) pre-1990 to 5.17 (95%CI 4.42–5.97) in 1990–2020 (p = 0.013). During the same time periods, no improvement was observed in the intra-operative cardiac arrest rates in low-HDI countries (p = 0.498). Odds ratios of intra-operative cardiac arrest rates in ASA 3–5 patients were 8.48 (95%CI 1.67–42.99) times higher in low-HDI countries than in high-HDI countries (p = 0.0098). Intra-operative cardiac arrest rates are related to country-HDI and decreased over time only in high-HDI countries. The widening gap in these rates between low- and high-HDI countries needs to be addressed globally.
Keywords: cardiac arrest; developed country; developing country; intra-operative period; meta-analysis